LBSL: Case Series and DARS2 Variant Analysis in Early Severe Forms With Unexpected Presentations. (April 2021) - Stellingwerff, Menno D.; Figuccia, Sonia; Bellacchio, Emanuele; Alvarez, Karin; Castiglioni, Claudia; Topaloglu, Pinar; Stutterd, Chloe A.; Erasmus, Corrie E.; Sanchez‐Valle, Amarilis; Lebon, Sebastien; Hughes, Sarah; Schmitt-Mechelke, Thomas; et al.
Abstract : Objective: Leukoencephalopathy with brainstem and spinal cord involvement and lactate elevation (LBSL) is regarded a relatively mild leukodystrophy, diagnosed by characteristic long tract abnormalities on MRI and biallelic variants in DARS2, encoding mitochondrial aspartyl-tRNA synthetase (mtAspRS). DARS2 variants in LBSL are almost invariably compound heterozygous; in 95% of cases, 1 is a leaky splice site variant in intron 2. A few severely affected patients, still fulfilling the MRI criteria, have been described. We noticed highly unusual MRI presentations in 15 cases diagnosed by WES. We examined these cases to determine whether they represent consistent novel LBSL phenotypes. Methods: We reviewed clinical features, MRI abnormalities, and gene variants and investigated the variants' impact on mtAspRS structure and mitochondrial function. Results: We found 2 MRI phenotypes: early severe cerebral hypoplasia/atrophy (9 patients, group 1) and white matter abnormalities without long tract involvement (6 patients, group 2). With antenatal onset, microcephaly, and arrested development, group 1 patients were most severely affected. DARS2 variants were severer than for classic LBSL and severer for group 1 than group 2. All missense variants hit mtAspRS regions involved in tRNA Asp binding, aspartyl-adenosine-5′-monophosphate binding, and/or homodimerization. Missense variants expressed in the yeast DARS2 ortholog showed severely affected mitochondrial function. Conclusions: DARS2 variants are associated with highly heterogeneous phenotypes. New MRI presentations are profound cerebral hypoplasia/atrophy and white matter abnormalities without long tract involvement. Our findings have implications for diagnosis and understanding disease mechanisms, pointing at dominant neuronal/axonal involvement in severe cases. In line with this conclusion, activation of biallelic DARS2 null alleles in conditional transgenic mice leads to massive neuronal apoptosis.